Analisis Asuhan Keperawatan Dengan Intervensi Aromaterapi Lavender terhadap Nyeri, Kelelahan, dan Suasana Hati (Mood) pada Ibu Post Partum - Resti Nurmelita; Eny Dewi Pamungkas (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
The postpartum period is a phase of maternal adaptation following childbirth. During this stage, mothers commonly experience various discomforts, including pain, fatigue, and mood disturbances. Lavender aromatherapy is one of the non-pharmacological interventions used to reduce pain and enhance emotional well-being by promoting comfort, openness, and a sense of reassurance. This study employed a case study design with a descriptive approach, implemented through the stages of the nursing care process using lavender aromatherapy as the primary intervention. The instruments used were the Visual Analog Scale (VAS) to assess pain and fatigue, and the Positive Affect Negative Affect Schedule (PANAS) to evaluate mood. Assessment and data analysis revealed that the primary nursing problems identified in both patients were acute pain and risk of infection, with an improvement in parental role readiness observed in the main case. Following the administration of lavender aromatherapy, both patients demonstrated reductions in pain and fatigue scores, as well as improvements in mood. Initially, pain and fatigue were categorized as moderate, but decreased to mild levels after the intervention, accompanied by an increase in positive affect. These findings indicate that lavender aromatherapy effectively reduces pain intensity, alleviates fatigue, and enhances mood among postpartum mothers.